Screening and Isolation of Antibiotic producing Microorganisms from Soil - Krishna, A. Ramya.; Aparna, Y. (International Journal of Scientific Research in Biological Sciences, 2019)
Diverse microorganisms are known to produce a wide variety of Antibiotics as secondary metabolites that are being developed and are used in treating various infections in humans, animals and plants. Microorganism has always been the primary source for production of antibiotics and still continues to maintain its significance. Antibiotics are produced by several group of microorganisms such as bacteria, fungi and actinomycetes. Abuse of antibiotics in various fields resulted in development of resistance in various bacteria which is a major threat in today’s scenario. Hence the screening of various antibiotics with effective antimicrobial activity is still continuing though thousands are available in today’s market. The present study was undertaken to screen various organisms from different sources for their antimicrobial activity. Samples were screened by crowded plate technique. Out of 10 samples screened only one soil sample from rhizosphere region has shown zone of inhibition. The organism was purified and tested for antimicrobial activity against E.coli sps, Pseudomonas sps, Bacillus, Klebsiella and Staphylococcus sps. The organism showed zone of inhibition only on gram positive bacteria. However maximum zone was observed with staphylococcus alone. Bacillus did not show significant inhibition. Further tests are being done to know the sensitivity of various staphylococcal strains of different origin with isolate.